Implementasi Pembayaran Zakat Perdagangan Oleh Pelaku Usaha Coffee Shop Di Kota Palembang - Beben Benardi; Lemiyana; Abubakar Sidik (GLOBAL SCIENTS PUBLISHER, 2025)
There are quite a lot of coffee shops in Palembang. There are 90 active Coffee Shops which can be seen from the Instagram account @liburhariselasa as a Coffee Shop review in Palembang, this is because there are many coffee lovers/visitors in the city of Palembang. With so many visitors coming to the coffee shop, it is not surprising that the profits earned by coffee entrepreneurs are so high, even the capital spent does not reach the income from the business. However, there are still entrepreneurs who do not understand and do not understand the zakat that must be paid on their income, there is income zakat or trade zakat that must be paid when the business has reached the calculation in Islamic Sharia. From the previous study, researchers were interested in researching the implementation of trade zakat by coffee shop business actors in Palembang.The type of research used in this research is qualitative research with a descriptive approach when presenting situations studied in the field, identifying problems that arise, and analyzing them in detail based on factual and accurate data. This research also uses Field Research or field research which means research in which data collection focuses on informants who have been determined.From the results of this research, it was noted that there were several coffee entrepreneurs in the city of Palembang who did not really understand the obligation to pay zakat on trade from an Islamic perspective. However, there are also business actors who understand their obligation to pay trade zakat, and have also carried out zakat payments in accordance with an Islamic perspective. Apart from that, there are also business actors who have paid trade zakat but the payment is not correct and not in accordance with Islamic law. Business actors who do not understand do not pay trade zakat in accordance with an Islamic perspective. In its implementation, the practice of paying trade zakat that has been carried out by the owner of Tjipta Djaja and Kopi Cepat is correct and in accordance with the ordered zakat payments, therefore, the payments made by coffee entrepreneurs are said to be in accordance with Islamic law. Meanwhile, Floor 4 Coffee already understands the understanding of trade zakat. but has not done so because his income has not met the nisab for calculating trade zakat. There are also coffee shop business actors who do not fully understand the payment of zakat on trade such as Dialek and Beruang Coffee.